Nicotine mediated epithelial modulations: An in-vitro evidence - Jigna Joshi; Apexa Pandit; Franky Shah (Elsevier, 2023)
Introduction: Nicotine, the main ingredient in tobacco, acts as a key alkaloid of nearly all tobacco products and has been demonstrated to facilitate tumorigenesis and accelerate metastasis. Further traditional tobacco products have shown to give systemic oral effects such as vasoconstriction, inflammation, and delayed wound healing, however; none of the reports have confirmed the significant knowledge of oral sequel of the effect of nicotine on oral epithelial cells. So, the current study aimed to investigate the effect of nicotine on epithelial transformation to a malignant state. Material & methods: Through in-vitro experiments, the effects of nicotine on epithelial cells obtained from nicotine never exposed buccal mucosa were analyzed using total count and viability test, proliferation assay, cell cycle distribution assay, and PI3K/MAPK dual pathway activation assay. Result & conclusion: MTT assay demonstrated that the proliferation of epithelial cells takes place at a 150 mM concentration of nicotine. Further, we identified the significantly increased cell count and viability in nicotine-exposed cells. Further, cell cycle distribution assay results demonstrated that nicotine forced the epithelial cells to enter the first growth phase. The same influence of nicotine was observed on the PI3K/MAPK dual pathway activation assay where a greater number of nicotine exposed cells showed dual pathway activation. In conclusion, the current study determined the potential mechanism of action of nicotine on oral epithelial cell proliferation through activating the oncogenic pathway. This may help to develop novel therapeutic strategies for the prevention of malignant transformation from smokeless tobacco-caused oral cancer.